Quodvultdeus’ sermons on the creed: A reassessment of his polemics against the Jews, pagans, and Arians - Vopřada, David (Vox Patrum, 2018)
The sermons of Quodvultdeus Bishop of Carthage during the time of the Vandal invasion of Africa are characterised by their harsh polemics against the Jews, Pagans, and Arians (De symbolo 1-3; Contra Iudaeos, paganos, et Arrianos; De accedentibus ad gratiam 1-2). The polemics against the Arians derived from the fact that the new lords of Africa, the Vandals, were Arians who promoted their belief and persecuted the Romans for professing their Catholic faith. This paper aims to reassess the polemical character of Quodvultdeus’ sermons. They are examined in their liturgical context and compared to other contemporary writings on the Creed, and finally discussed in their historical and religious context. In view of this analysis, it can be stated that the works of Quodvultdeus studied here are not primarily anti-heretical, but they rather focus on affirming the doctrine of the Church and on the adherence of the newly baptised to the Church as a means of salvation. Quodvultdeus’ harsh anti-heretical language is not exceptional in the Latin tradition of creedal catechesis during the 4th and 5th centuries and has therefore chiefly a catechetical function.